The quality of physical education in higher education in China - Yan, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: There have been many changes in physical education in higher Education in China, and therefore the quality of assessment should be reviewed accordingly. This evaluation is considered necessary to promote the appropriate development of quality physical education programs at this level. Methods A review of literature was the main research method, and documents from within local organizations on physical education and the quality of higher education were collected and analyzed. Results / Discussion Documentation showed recognition of the importance of Physical education in the higher education system of China and advancements in scientific research into the benefits of PE create the basis for the rapid development of physical education in higher education. At this level, physical education has developed and evolved, with changes in the attitudes of students, parents and the market further supporting the need for assessment of its quality and adjustment of needs accordingly. The review identified 3 basic problems requiring attention in Chinese PE in higher education. 1. Although PE in Chinese higher education Institutions has advanced to a stage where it is widely accepted, there are still some negative attitudes towards it. Therefore the most important issue in physical higher education is improving the quality of education and changing people`s attitudes. 2. PE in higher education is unbalanced in certain social, cultural and economic backgrounds, and a more equitable and uniform quality standard should be developed. 3. With this background physical education in higher education in China, should be evaluated regularly by governments to ensure that quality is controlled and the goals of higher education are met.